Optimization of Thermal Conductivity and Latent Heat Capacity Using Fractional Factorial Approach for the Synthesis of Nano-Enhanced High-Performance Phase-Change Material - Mohan, Man; Dewangan, Sheetal Kumar; Lee, Kwan; Ahn, Byungmin (International Journal of Energy Research, 2024)
This study systematically optimizes the synthesis parameters for nano-enhanced phase-change materials (NEPCMs) based on paraffin wax and copper oxide. The objective is to collectively improve both thermal conductivity and latent heat capacity. Unlike the previous research, the present approach considers all significant synthesis parameters simultaneously, employing a fractional factorial approach for efficient experimentation. By varying CuO nanoparticle sizes, paraffin wax melting temperatures, and mass fractions of CuO and surfactant in pure paraffin wax, the comprehensive thermal analysis reveals a maximum enhancement of 51.2% thermal conductivity compared to pure paraffin wax. In addition to thermal conductivity improvement, the applied optimization strategy identifies six NEPCM combinations, collectively enhancing thermal conductivity, latent heat of melting, and solidification. Among these, one NEPCM exhibits notable improvements of 13.39%, 6.9%, and 4.5% in thermal conductivity, latent heat of melting, and solidification, respectively, making it suitable for thermal energy storage systems due to combined enhanced thermal properties. Additionally, the ANOVA approach indicates the melting temperature of pure PCM as the most significant factor for thermal conductivity enhancement, with a contribution of 55.45%. The present study has a direct impact on improving thermal properties, specifically in thermal energy storage technology, making it relevant to the thermal management research community.
Keywords: Fractional factorials; Latent heat of melting; Material-based; Melting and solidification; Optimisations; Performance; Phase Change; Property; Synthesis parameters; Thermal